(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to determine Adaptive Governance in Capacity Building of Local Governments in Empowering Street Vendors (PKL). This study used descriptive qualitative. This type of research was qualitative. Data sources consisted of Primary data and Secondary data. The number of informants in this study were 7 (seven) people from 6 (six) agencies. The results of this study indicated that Adaptive Governance in the Capacity Development of Local Governments in Street Vendors Empowerment (PKL) had been running well as evidenced by the development of street vendors no longer using public roads to trade. Although there was little that needed to be addressed so that street vendors were satisfied with the results of government work. The influencing factor was the government providing a new location for street vendors to trade and no longer using public roads that disturbed road users.